Measurement of Excess Pore-Water Pressure in Frozen Soil at Subfreezing Temperatures Close to 0°C - Hu Zhang; Suiqiao Yang; Huijun Jin; Mengxin Liu (Geofluids)
Response of pore-water pressure has crucial effect on the engineering geological performance of permafrost ground. However, there is a dearth of literature on the measurement of pore-water pressure in frozen soils due to challenges with regard to technical and operational method. To validate the generation of pore-water pressure and to reveal its variation property in frozen soils at subfreezing temperatures close to 0°C, a miniature pressure transducer was utilized to conduct a number of confined compression tests. Double-wall structure avoided damage to the transducer during frozen soil sampling. The transducer at sample bottom perceived a pressure fluctuation as varying air pressure imposed on sample surface, proving the connectivity among the pores in frozen soils with a hysteretic effect on pressure transmission. Pore-water pressure experienced a progressive increase followed by a slow dissipation under invariable load and temperature conditions when water drainage was permitted, while a monotonic increase in pressure was observed for an undrained sample. With decreasing temperature, a smaller peak and a more dilatory dissipation were displayed. When the sample was exposed to a stepwise warming process, a similar performance for the pressure was obtained with abrupt rise at the turning point of temperature.